Circulating endothelial cells (CECs) and E-selectin: Predictors of preeclampsia - Ferdous Mehrabian; Sayed Mohammad Hashemi Jazi; Shaghayegh Haghjooy Javanmard; Mahshid Kaviani; Vida Homayouni (Journal of Research in Medical Sciences, 2012)
Background: Circulating endothelial cells (CECs) and E-selectin are known as sensitive and specific markers of en-dothelial dysfunction. This study investigated whether CECs and E-selectin are surrogate biomarkers of preeclampsia and if measurement of CECs and E-selectin, early in the third trimester, could be a means of predicting preeclampsia. Methods: In this prospective, descriptive-analytic study, rollover test was performed on 523 pregnant women during 28-30 weeks of gestation. CECs were measured by anti-CD 146-driven immunomagnetic isolation in women with posi-tive rollover test. They were followed up prospectively until delivery without any active intervention. Women with and without preeclampsia were determined. The number of CECs and level of E-selectin were compared in the two studied groups. Results: From the 47 pregnant women with positive rollover test who were selected and followed up, 22 individuals were diagnosed with preeclampsia while the remainder were normotensive. Mean CEC numbers was significantly high-er in preeclamptic women than normal pregnancies (24.7 cells/mL vs. 13 cells/mL). The best cut-off point for CEC numbers was 6.5 with a sensitivity of 78.9% and a specificity of 69.1%. The level of E-selectin was significantly higher in mothers with preeclampsia (p < 0.05). Conclusions: Higher levels of CECs and E-selectin in women with positive rollover test who developed preeclampsia prior to onset of the complication were predictive of preeclampsia. However, larger studies are needed to confirm these findings.